Mechanical Properties, Impermeability, and Microstructure of Mortar Containing Recycled Fine Aggregates Modified by Graphene Oxide After High-Temperature Exposure - Zhao Xiang; Guofu Chen; Zhiwei Cai; Jiaxing Shao (Buildings)
Graphene oxide (GO) has been verified to ameliorate the performance attenuation of cement-based materials exposed to high temperatures; however, its efficacy on cement-based materials containing recycled fine aggregates (RFAs) remains ambiguous. Therefore, this study assesses the macro/microperformance variations in mortar containing RFAs with diverse GO dosages (0~0.08%) after high-temperature exposure. The hydration products, pore structure, and microstructure of mortar containing RFAs and GO were analyzed using an X-ray diffractometer, mercury intrusion porosimetry, and scanning electron microscopy, respectively. The study finds that GO can reduce the mass loss rate of mortar exposed to high temperatures and enhance the residual compressive strength and flexural strength. The incorporation of 0.06% GO leads to a 10.4% increase in compressive strength and a 32.3% increase in the flexural strength of mortar containing 50% RFA after high-temperature exposure at 500 °C. Furthermore, the incorporation of GO refined the pore size and improved the densification of the interfacial transition zone (ITZ) of the mortar after high-temperature exposure. Taking into account the mechanical properties, water absorption, and microstructure of the mortar containing RFAs, a GO dosage of 0.04~0.06% could be recommended as the optimum engineering dosage.